Role of Library and Information Professionals in Protection of Intellectual Property (IPR) - Kamble, Sangeeta (Journal of Advanced Research in Library and Information Science; Vol 7 No 2 (2020): Journal of Advanced Research in Library and Information Science, 2020)
The aim of this article is to explain concepts like IPR, copyright, digital rights. This paper highlights the role of library professionals in the protection of IPR. Here the author tries to explain how libraries can get the ultimate usage of the resources within the limits of intellectual property rights. It concluded that the library and information professionals should have full knowledge of IPR to keep the safeguard of the user community. It also throws light on the duties and responsibilities of library professionals in the preservation of intellectual properties in the library.